Edukasi Pencegahan dan Penanganan Hipertensi pada Warga Dusun Plumpung Desa Galengdowo - Az Zahra, Maulidya Rachma; Nungky Taniasari (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Hypertension is a growing health problem, especially among the elderly and low-educated communities. Hypertension continues to emerge as a critical public health challenge, with increasing incidence and uneven impact, particularly affecting the elderly population and low-educated communities. In response to this situation, a community-based study was conducted in Plumpung Hamlet, Galengdowo Village, with the main objective of increasing residents' knowledge and awareness of primary prevention strategies and self-management of hypertension. The intervention method applied was multimodal, including interactive health lectures, distribution of leaflets designed with easy-to-understand language and clear visuals, and provision of free blood pressure checks that served as a screening tool and immediate awareness. This research design used a participatory approach with pre-test and post-test instruments to measure quantitative changes in participants' understanding, accompanied by blood pressure monitoring activities to evaluate the impact of education on physical health indicators. The evaluation results showed the program's significant success, marked by a 57.69% increase in comprehension scores between the pre-test and post-test sessions, while also showing an improvement trend in the blood pressure values of most participants after completing the entire education series. These findings clearly affirm the fundamental role of sustainable and accessible health education as an effective community-based intervention to mitigate hypertension risk factors and ultimately improve holistic quality of life. The implications of this study highlight the urgency of implementing regular, structured, and targeted education programs, especially those targeting the most vulnerable demographic groups, as a long-term health investment to prevent morbidity and complications from hypertension.